An Analysis of Carnation Cut Flower Market in Kathmandu Valley, Nepal (Economic Journal of Nepal, 2020)
Carnation is an important cut flower commercially traded in Kathmandu Valley. It has high demand of floriculture market in the Kathmandu Valley due to its physical characteristics and also its suitability to be used singly or in combination with other flowers in different floriculture products. So, the study has attempted to analyze the market of carnation cut flower in Kathmandu Valley. Data were collected from sample of carnation producers, wholesalers, retailers, and consumers of the Kathmandu Valley. Simple random sampling technique was employed to select the respondents. Information from the respondents was generated through semi-structured interview schedule. Key informants were also interviewed for in-depth and related information. Data collected through personal interview and secondary sources was analyzed by applying descriptive statistical tools. Data analysis focused mainly on the market structure, conduct of marketing agents, and performance of carnation cut flower in the market in terms of returns to the marketing agents, present problems in marketing, and future prospects of carnation in Kathmandu Valley. Findings reveal that the market structure was well integrated and the conduct of the marketing actors was so far competitive to the large extent. The performance of the carnation cut flower in terms of price and profit seems satisfactory and sustainable. However, there were ample areas of improvements in the marketing system. Given the high degree of demand in the valley and increasing trend of imports of carnation cut flowers from other districts of the country as well as from foreign countries, concerted efforts must be made to reverse the situation and make the Valley self-reliant in fulfilling its demand alongside exporting to other districts and countries in the future.